Cachexia in chronic obstructive pulmonary disease: new insights and therapeutic perspective. Issue 1 (7th September 2015) - Sanders, Karin J. C.; Kneppers, Anita E. M.; van de Bool, Coby; Langen, Ramon C. J.; Schols, Annemie M. W. J.
Abstract: Cachexia and muscle wasting are well recognized as common and partly reversible features of chronic obstructive pulmonary disease (COPD), adversely affecting disease progression and prognosis. This argues for integration of weight and muscle maintenance in patient care. In this review, recent insights are presented in the diagnosis of muscle wasting in COPD, the pathophysiology of muscle wasting, and putative mechanisms involved in a disturbed energy balance as cachexia driver. We discuss the therapeutic implications of these new insights for optimizing and personalizing management of COPD‐induced cachexia.